Maintaining sinus rhythm after electrical cardioversion. (14th October 2021) - Menezes Fernandes, R; Mota, T.F; Costa, H.A; Espirito Santo, M; Bento, D; Candeias, R; Mimoso, J; Jesus, I
Abstract: Introduction: Atrial fibrillation (AF) and atrial flutter (AFL) are commonly terminated by electrical cardioversion (EC) when a rhythm control strategy is adopted. However, the long-term success following EC is variable. Purpose: To determine the clinical characteristics and independent predictors of sinus rhythm (SR) maintenance after EC due to AF/AFL. Methods: We conducted a retrospective study enrolling patients with AF/AFL referred to EC in our Cardiology Department, from September 2011 to September 2020. Clinical characteristics and echocardiographic studies were analysed. Primary endpoints were the incidence of ischemic stroke, all-cause and cardiovascular (CV) mortality. Independent predictors of SR maintenance were identified through a binary logistic regression analysis, considering p=0, 05. Results: A total of 719 patients with a median age of 67 years-old were included, and EC was successfully performed in 93, 2%. AFL was diagnosed in 21%, 57, 3% had arterial hypertension and 34, 6% were obese. 62, 1% had persistent AF/AFL, 19, 6% presented with first diagnosed AF/AFL and 17, 2% had paroxysmal episodes. Left ventricular ejection fraction (LVEF) was preserved in 66, 7%. Maintenance of SR after one-year was documented in 64, 7% of patients with successful EC. They had lower prevalence of chronic kidney disease (CKD) (2, 6% vs 10, 7%; p<0, 001) and received less electrical shocks during EC (1, 20 vs 1, 39; p=0, 005). There were no differences regarding antiarrhythmic therapy between both groups. Complete LVEF recovery after EC was more frequent in patients who maintained SR (58, 8% vs 31, 9%; p=0, 008), with a greater prevalence of preserved LVEF after EC (88, 8% vs 73, 6%; p<0, 001). During a median follow-up of 1368 days, these patients performed less additional EC (0, 26 vs 0, 65; p<0, 001) and were less referred to ablation procedures (7, 1% vs 15, 1%; p=0, 011). No differences were found regarding stroke rate, but all-cause mortality (12, 8% vs 25%; p=0, 002) and CV death (3, 8% vs 10, 9%; p=0, 005) were significantly lower in patients who maintained SR. Absence of CKD (p=0, 013), applying fewer electric shocks during EC (p=0, 013) and preserved LVEF after EC (p=0, 004) were independent predictors of SR maintenance. Conclusion: In our study, most patients maintained SR one year after EC, which was associated with a lower all-cause and CV mortality. Absence of CKD, applying fewer electric shocks during EC and preserved LVEF after EC were independent predictors of SR maintenance. Funding Acknowledgement: Type of funding sources: None.